Late Recovery from Severe Streptococcus pneumoniae Comatose Meningitis with Concomitant Diffuse Subcortical Cytotoxic Edema and Cortical Hypometabolism - Philippe Hantson; Thierry Duprez (Case Reports in Neurological Medicine)
A 75-year-old woman was admitted to ICU with coma following Streptococcus pneumoniae meningitis with bacteremia. Her Glasgow Coma Scale (GCS) score fluctuated around 4 to 6 over the next four weeks. There was no evidence of increased intracranial pressure (ICP). Electroencephalogram (EEG) showed only diffuse aspecific slowing. Impaired cerebral blood flow (CBF) autoregulation was suggested at transcranial Doppler (TCD). Repeated brain magnetic resonance imaging (MRI) examination failed to demonstrate venous thrombosis, arterial ischemic stroke, or brain abscesses but revealed diffuse but reversible cortical cytotoxic edema at diffusion-weighted (DW) sequences. The brain FDG-positron emission tomography (FDG-PET) showed diffuse cortical hypometabolism. The patient unexpectedly experienced a complete neuropsychological recovery the next few weeks. The suggested hypothesis to explain this unusual disease course could be a transient alteration of CBF autoregulation due to some degree of diffuse subcortical microangiopathy. A concomitant reduction of brain metabolism probably prevented the progression towards cortical irreversible ischemic damage.